2022
DOI: 10.3390/ijms24010068
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CDKL5 Causes Synaptic GABAergic Defects That Can Be Restored with the Neuroactive Steroid Pregnenolone-Methyl-Ether

Abstract: CDKL5 deficiency disorder (CDD) is an X-linked neurodevelopmental disorder characterised by early-onset drug-resistant epilepsy and impaired cognitive and motor skills. CDD is caused by mutations in cyclin-dependent kinase-like 5 (CDKL5), which plays a well-known role in regulating excitatory neurotransmission, while its effect on neuronal inhibition has been poorly investigated. We explored the potential role of CDKL5 in the inhibitory compartment in Cdkl5-KO male mice and primary hippocampal neurons and foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In our work we have studied the neurometabolic component of four neurodevelopmental diseases in which the main described element of their pathophysiology is an altered glutamatergic neurotransmission. For that, we have analyzed cerebrospinal fluid 29 samples from patients and controls distributed in three different groups: (a) patients with conditions associated to increased glutamatergic activity (mutations in MECP2 35 and CDKL5 36 ), (b) patients with encephalopathies associated to hypoglutamatergic activity (with mutations in STXBP1 22 and the GRIN 20 genes) and (c) controls. Rett syndrome and related disorders have shown vast evidence of altered glutamatergic neurotransmission, including higher levels of glutamate and a reduced expression of metabotropic glutamate receptors 5 and 7 (mGlu5, mGlu7), 37,38 alterations in NMDA receptors expression or elevated glutamate release 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In our work we have studied the neurometabolic component of four neurodevelopmental diseases in which the main described element of their pathophysiology is an altered glutamatergic neurotransmission. For that, we have analyzed cerebrospinal fluid 29 samples from patients and controls distributed in three different groups: (a) patients with conditions associated to increased glutamatergic activity (mutations in MECP2 35 and CDKL5 36 ), (b) patients with encephalopathies associated to hypoglutamatergic activity (with mutations in STXBP1 22 and the GRIN 20 genes) and (c) controls. Rett syndrome and related disorders have shown vast evidence of altered glutamatergic neurotransmission, including higher levels of glutamate and a reduced expression of metabotropic glutamate receptors 5 and 7 (mGlu5, mGlu7), 37,38 alterations in NMDA receptors expression or elevated glutamate release 39 .…”
Section: Discussionmentioning
confidence: 99%
“…A phosphospecific antibody for EB2-S222 has been used to report CDKL5 activity in mouse models and human iPSCs ( Baltussen et al, 2018 ; Terzic et al, 2021 ; Di Nardo et al, 2022 ). CDKL5 is a binding partner of both PSD-95 and gephyrin ( Uezu et al, 2016 ; De Rosa et al, 2022 ); binding with PSD-95 is critical for excitatory spine synapse development ( Wang et al, 2012 ) and maintenance of inhibitory synapses ( De Rosa et al, 2022 ). Studies have typically found that loss of CDKL5 leads to a global reduction in excitatory synapse numbers ( Ricciardi et al, 2012 ; Della Sala et al, 2016 ), reduced PSD-95 ( Negraes et al, 2021 ; Lupori et al, 2019 ), and synapsin ( Negraes et al, 2021 ) with loss of AMPA-type glutamate receptors (GluA2; Yennawar et al, 2019 ) and increased NMDA-type glutamate receptors (GluN2B; Okuda et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have typically found that loss of CDKL5 leads to a global reduction in excitatory synapse numbers ( Ricciardi et al, 2012 ; Della Sala et al, 2016 ), reduced PSD-95 ( Negraes et al, 2021 ; Lupori et al, 2019 ), and synapsin ( Negraes et al, 2021 ) with loss of AMPA-type glutamate receptors (GluA2; Yennawar et al, 2019 ) and increased NMDA-type glutamate receptors (GluN2B; Okuda et al, 2017 ). Inhibitory synapses appear to be unaffected ( Ricciardi et al, 2012 ), although inhibitory synaptic currents are affected in some CDKL5 mouse models ( De Rosa et al, 2022 ; Tang et al, 2017 ). Embryonic knock-out of Cdkl5 rodents either enhanced long-term potentiation (LTP) ( Okuda et al, 2017 ; de Oliveira et al, 2022 ) or did not affect LTP ( Yennawar et al, 2019 ; de Oliveira et al, 2022 ) in an age-dependent fashion.…”
Section: Introductionmentioning
confidence: 99%